MAQASID UMUM HUKUM ISLAM DALAM PENYELESAIAN HARTA BERSAMA PASCA PERCERAIAN: SUATU KAJIAN NORMATIF - Luvia Wahid; Nuril Khasyi’in (PT. Hasba Edukasi Mandiri, 2026)
Data from the Religious Courts shows that disputes over marital property constitute one of the most frequently filed follow-up claims after a divorce decision becomes final and binding. These cases indicate that issues of marital property are not merely technical matters of asset division, but also relate to the protection of rights and legal certainty for vulnerable parties after divorce. The positive legal framework that serves as the basis for judges, particularly the Compilation of Islamic Law (KHI), remains very general and provides insufficient detailed parameters. This study employs a normative legal research method focusing on the examination of norms, principles, and legal doctrines related to the settlement of marital property after divorce from the perspective of maqāṣid al-sharī‘ah. The approaches used include conceptual, statutory, and comparative approaches. The analysis of legal materials is conducted deductively. The findings show that the integration of maqāṣid enables judges to carry out contextual assessments of non-material contributions, supports a distribution that is responsive to the economic vulnerability of the weaker party, and encourages the need for clearer evidentiary guidelines and judicial policies to ensure consistency of rulings. Thus, the maqāṣid approach not only provides philosophical legitimacy for the practice of marital property division in Indonesia but also offers a practical normative framework to ensure that post-divorce asset distribution upholds the principles of public interest and proportional justice.